Patient and Family Experience: Targets for Improvements in Care and Communication in the ICU - Caitlin A. LaGrotte PsyD, MEd; Caitlin Baldwin DO; Krystal Hunter PhD, MBA; Emily Damuth MD; Nancy Loperfido BS; Tatheer Moosavi BA; Pearl Parker BA; Nitin Puri MD (Journal of Patient Experience)
This process improvement project sought to further explore the experience of patients and family members within an intensive care unit (ICU) hospital setting to develop specific interventions that can be executed to provide better patient-centered outcome. We surveyed 103 family members using the satisfaction with care subscale of Family Satisfaction with the ICU survey (FS-ICU) (validated ICU experience survey). 103 patients also completed FS-ICU subscale with a modification to make it applicable to patients. Additional questions explored their interest in supportive services and factors contributing to distress with the goal of understanding the gaps in multidisciplinary care and supportive services. Overall, the findings of this project emphasize the importance of (1) understanding patients’ experience and satisfaction with care, in addition to families’, (2) gathering data with measurement tools that is specific enough to the care environment allowing for unique feedback and areas for improvement, and (3) identifying psychological needs and faith-based support to intervene on challenging experiences.